Privacy and housing modifications among Malay urban dwellers in Selangor - Hashim, Ahmad Hariza; Abdul Rahim, Zaiton (Universiti Putra Malaysia Press, 2010)
This research examined the privacy needs of the Urban Malays in Malaysia and focuses on the medium cost two-storey terrace housing typology. The literature review indicated that low priority was given for privacy in the traditional Malay society which emphasises more on community intimacy, which subsequently influences their housing design. The National Economic Policy in the 1970s encouraged the rural-urban migration among the rural Malays, which indirectly changed their way of lives and their housing environment, especially when many of these new migrants lived in terrace housing. An earlier study indicated that the earlier generations have maintained their cultural values, while there are studies which show that neighbourhood ties among the urban Malays are weakening and family privacy has become more important. This study involved 401 respondents, selected at random from among heads of households living in Selangor, Malaysia. Two areas involved in this study, namely Gombak and Kajang in the district of Hulu Langat, were selected at random. The survey method using questionnaire and in-depth interview with selected respondents were employed to examine the meaning of privacy and the influence of privacy on housing modifications. The findings indicated that the meanings of privacy were influenced by their cultural norms and religious belief, which were unlike what was being practiced by the traditional society and in the village housing setting. The study also revealed that the privacy provided by the original designs was not sufficient and that the need to provide privacy is one of the main reasons for housing modifications.